Pay (Be)for(e) Performance: The Signing Bonus as an Incentive Device - Van Wesep, Edward Dickersin (Review of Financial Studies, 2010)
The signing bonus is one of the most common elements of compensation packages for white-collar employees but has received little theoretical and empirical attention. This article investigates the use of a signing bonus as a tool for firms to signal to prospective employees: when they are uncertain regarding their fit with the firm, the signing bonus can serve as a credible signal of the firm's belief of said fit. The theory suggests that we should expect signing bonuses to be more common and larger when the economy is stronger, when employees are less certain of how well they will fit at the firm, when the quality of fit (known to the firm) is higher, and when performance pay is present. Employees receiving a signing bonus work harder, so the signing bonus also serves as an incentive device. This article also presents the first broad empirical look at the use of the signing bonus across industries and time. Evidence is consistent with the theory. The Author 2010. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oxfordjournals.org., Oxford University Press.